Investigating Nutrient Supply Effects on Plant Growth and Seed Nutrient Content in Common Bean - Millicent R. Smith; Barbara Elias Reis Hodecker; David Fuentes; Andrew Merchant (Plants, 2022)
Low soil fertility commonly limits growth and yield production of common bean (Phaseolus vulgaris L.) in tropical regions. Impacts of nutrient limitations on production volume are well studied and are a major factor in reducing crop yields. This study characterised the impact of reduced nutrient supply on carbon assimilation and nutrient content of leaf, phloem sap and reproductive tissues of common bean grown in a controlled environment in order to detect chemical markers for changes in nutritional content. Leaf gas exchange measurements were undertaken over plant development to characterise changes to carbon assimilation under reduced nutrient supply. Samples of leaf, phloem sap and pod tissue of common bean were analysed for carbon isotope discrimination, mineral nutrient content, and amino acid concentration. Despite declines in nutrient availability leading to decreased carbon assimilation and reductions in yield, amino acid concentration was maintained in the pod tissue. Common bean can maintain the nutritional content of individual pods under varying nutrient availabilities demonstrating the resilience of processes determining the viability of reproductive tissues.